GCT-05. Multi-institutional analysis of treatment modalities in metastatic germinoma in children. (3rd June 2022) - Shatara, Margaret; Abu-Arja, Mohammad H; MacDonald, Shannon; Reiners, Stephanie; Gorsi, Hamza; Govender, Dinisha; Dholaria, Hetal; Nagabushan, Sumanth; Schwartz, Jonathan; Foo, Jen Chun; Rajagopal, Revathi; Perkins, Stephanie; et al.
Abstract: BACKGROUND: Primary intracranial germ cell tumors (GCTs) are rare heterogeneous tumors, with germinoma accounting for two-thirds of cases. Neoadjuvant chemotherapy with response-based reduced radiotherapy dose and field has become the standard management of localized CNS germinomas, however, treatment of primary metastatic disease has remained controversial. Furthermore, there is limited published research on the use of neoadjuvant chemotherapy in primary metastatic germinoma. METHODS: We performed a retrospective multi-institutional data collection and analysis of patients diagnosed with metastatic germinoma since 2000 to assess the overall survival (OS) and event-free survival (EFS) of the different treatment modalities administered. RESULTS: We identified 78 patients with germinoma, in two tertiary care centers, of which nine patients (11.5%; eight males) had metastatic disease. The median age at presentation was 13.3 years. All patients had a biopsy at presentation confirming the diagnosis. Three patients had positive CSF cytology (M1). Six patients received craniospinal irradiation (CSI) with boost to primary and metastatic sites, of which five patients received total CSI dose of 24 Gy, while the dose was unknown for one patient. One patient required one cycle of chemotherapy prior to CSI due to worsening visual changes, which subsequently resolved. One patient received two cycles followed by whole ventricular irradiation (WVI) of 23.4 Gy with a boost to the primary bed. One patient received WVI without neoadjuvant chemotherapy. One patient developed anoxic brain injury and only received chemotherapy. He died of recurrent progressive disease 15 months post-diagnosis. The median follow-up time was 77.5 months (range 15-130.5 months), with an OS of 88.9%. Further multi-institutional data collection and analysis is underway and will be presented at the meeting. CONCLUSION: We anticipate our results may elucidate the role of neoadjuvant chemotherapy in the treatment of metastatic germinoma, and whether when combined with lower CSI doses did not compromise EFS/OS.